2019
DOI: 10.3892/mmr.2019.10719
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant betatrophin (Angptl‑8/lipasin) ameliorates streptozotocin‑induced hyperglycemia and β‑cell destruction in neonatal rats

Abstract: Betatrophin [also known as lipasin, angiopoietin-like 8 (ANGPTL8), refeeding induced in fat and liver (RIFL), or hepatocellular carcinoma-associated gene TD26], a 22-kDa protein in the angiopoietin-like family, is a liver-derived hormone that promotes pancreatic β-cell proliferation and lipid metabolism. The aim of the present study was to investigate the effect of recombinant betatrophin on β-cell regeneration in a neonatal streptozotocin (STZ)-induced diabetic rat model. One-day-old Wistar rats were injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…ANGPTL8/betatrophin seemes to be a pleiotropic hormone, as it was reported to regulate both lipid and glucose metabolism [2][3][4][5][6], and was recently reported to act as a moderate suppressor of human liver carcinoma cells [19]. ANGPTL8/betatrophin is not only enriched in the liver but is also reported to be expressed at significantly higher levels in hepatocellular carcinoma patients than in healthy controls [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANGPTL8/betatrophin seemes to be a pleiotropic hormone, as it was reported to regulate both lipid and glucose metabolism [2][3][4][5][6], and was recently reported to act as a moderate suppressor of human liver carcinoma cells [19]. ANGPTL8/betatrophin is not only enriched in the liver but is also reported to be expressed at significantly higher levels in hepatocellular carcinoma patients than in healthy controls [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was referred to as ANGPTL8/betatrophin. Previous studies have shown that ANGPTL8/betatrophin is involved in the regulation of both lipid metabolism and glucose homeostasis [3][4][5][6]. It is well known that cancer cells change their metabolism to support rapid proliferation and expansion; hence, abnormal lipid and glucose metabolism has been found to be involved in a variety of cancers [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the mice were sacrificed by exsanguination following an intraperitoneal injection of 50 mg/kg sodium pentobarbital. Blood samples were obtained from the orbital sinus and stored at −20°C or −80°C until further use ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%